Enhancement of Anticancer Efficacy and Tumor Penetration of Sorafenib by Ionic Liquids. Issue 2 (17th November 2020) - Shi, Yujie; Zhao, Zongmin; Peng, Kevin; Gao, Yongsheng; Wu, Debra; Kim, Jayoung; Mitragotri, Samir
Abstract: Ionic liquids (ILs) possess unique solvation and biological properties for drug delivery. Choline and geranic acid (CAGE) in particular, has been successfully formulated to orally deliver insulin and hydrophobic therapeutics such as sorafenib (SRF). However, relatively little is known about the effect of CAGE on intracellular delivery of drugs. Here the effect of low‐concentration CAGE (<2 mg mL −1 ) on the delivery of SRF into cancer cells (4T1, PANC‐1, and HT29) as well as intestine epithelium cells (Caco‐2) is studied. The anti‐cancer effect of SRF is enhanced by up to fivefold in the presence of CAGE (0.5 mg mL −1 ). The effect is mediated not by enhancing the cellular uptake of SRF but by improving intracellular SRF retention by inhibiting exocytosis. Moreover, CAGE improves the anti‐tumor effect of SRF by increasing apoptosis and blocking cell‐cycle progression. Moreover, CAGE significantly enhances the penetration of SRF into and across multicellular constructs with multiple mechanisms involved. Collectively, the administration of ILs such as CAGE combined with SRF may offer a novel therapy to better inhibit tumor progression. Abstract : This work studies the effect of low‐concentration choline and geranic acid (CAGE) on intracellular delivery sorafenib (SRF). CAGE improves the anti‐cancer effect of SRF up to fivefold by enhancing intracellular SRF retention, increasing apoptosis, blocking cell‐cycle progression, significantly enhancing the penetration of SRF into and across multicellular constructs with multiple mechanisms involved. CAGE combined with SRF offers a novel therapy to inhibit tumor progression.